Lipid-based nanoparticles and RNA as innovative neuro-therapeutics - Tsakiri, Maria; Zivko, Cristina; Demetzos, Costas; Mahairaki, Vasiliki (Frontiers in Pharmacology, 2022)
RNA-delivery is a promising tool to develop therapies for difficult to treat diseases such as neurological disorders, by silencing pathological genes or expressing therapeutic proteins. However, in many cases RNA delivery requires a vesicle that could effectively protect the molecule from bio-degradation, bypass barriers ie., the blood brain barrier, transfer it to a targeted tissue and efficiently release the RNA inside the cells. Many vesicles such as viral vectors, and polymeric nanoparticles have been mentioned in literature. In this review, we focus in the discussion of lipid-based advanced RNA-delivery platforms. Liposomes and lipoplexes, solid lipid nanoparticles and lipid nanoparticles are the main categories of lipidic platforms for RNA-delivery to the central nervous systems (CNS). A variety of surface particles’ modifications and routes of administration have been studied to target CNS providing encouraging results in vivo. It is concluded that lipid-based nanoplatforms will play a key role in the development of RNA neuro-therapies.